Evaluasi Program Ruang Publik Terpadu Ramah Anak (RPTRA) Guna Pemenuhan Hak Anak Di Daerah Khusus Ibukota Jakarta (Studi Kasus RPTRA Bandar Kemayoran Kota Administrasi Jakarta Pusat) - Lastiani, Frida (CV RIFAINSTITUT, 2023)
The study examines the effectiveness of the Children-Friendly Integrated Public Space Program's effectiveness in fulfilling children's rights in the Jakarta Special Capital Region. Specifically, the research focuses on the RPTRA Bandar Kemayoran program in Central Jakarta Administrative City due to the increasing teenage delinquency and criminal involvement of children, as well as the need to maximize the use of public spaces after the COVID-19 pandemic. Using a qualitative-descriptive approach, the study analyzes the program's progress and evaluates its impact through interviews, field observation, and desk study results. The study involves six informants who provide valuable insights. Results indicate that the implementation of the RPTRA program has positively impacted meeting the rights of children in the RPTRA Bandar Kemayoran, as evidenced by its progress in terms of context evaluation, inputs, process, and outputs.